2022
DOI: 10.3803/enm.2022.1427
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Safety and Effectiveness of Denosumab in Patients with Osteoporosis: A Prospective, Observational Study in South Korea

Abstract: Background: The efficacy and safety of denosumab have been established in a phase 3, randomized, placebo-controlled trial in Korean postmenopausal women with osteoporosis. This postmarketing surveillance study was aimed to investigate the safety and effectiveness of denosumab in Korean real-world clinical practice.Methods: Patients with osteoporosis who had received denosumab per the Korean approved indications in the postmarketing setting between September 2014 and September 2019 were enrolled. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The prevalence of hypocalcemia was higher in our study (6%) than in the original clinical trial (FREEDOM), which reported a prevalence of 0–0.1% [ 4 , 6 ]. A low prevalence of hypocalcemia (< 1% hypocalcemia) was also reported in the FREEDOM sub-analysis of patients with renal failure and in a post-marketing real-world prospective observational trial [ 12 , 17 ]. Our findings are in the same range as other large-scale studies on real-world cohorts, which reported the frequency of denosumab-induced hypocalcemia to range from 4 to 8% [ 7 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The prevalence of hypocalcemia was higher in our study (6%) than in the original clinical trial (FREEDOM), which reported a prevalence of 0–0.1% [ 4 , 6 ]. A low prevalence of hypocalcemia (< 1% hypocalcemia) was also reported in the FREEDOM sub-analysis of patients with renal failure and in a post-marketing real-world prospective observational trial [ 12 , 17 ]. Our findings are in the same range as other large-scale studies on real-world cohorts, which reported the frequency of denosumab-induced hypocalcemia to range from 4 to 8% [ 7 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 84%
“…Using non-routine data, i.e., calcium analysis only if doctors ask for it [ 17 ], might include selection bias where only high-risk patients are followed up with calcium measurements. This might yield an overestimation of the prevalence of hypocalcemia, or it might risk missing cases of mild hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…32 Therefore, in choosing osteoporosis treatments, the potential for increased adverse event risks associated with denosumab may not be a primary concern. 33,34 Given the high osteoporosis prevalence, the extensive use of antiosteoporosis medications, and the negative effect of diabetes on both patient health and health care system burdens in the global aging population, our findings possess substantial clinical and public health significance.…”
Section: Discussionmentioning
confidence: 89%
“…Osteoporosis decreases bone strength, subsequently increasing the risk of fracture and leading to notable morbidity and diminished quality of life. Denosumab, the first-approved biologic agent for the treatment of osteoporosis, is a potent antiresorptive drug that can significantly reduce the risk of hip, vertebral, and non-vertebral fractures [ 2 , 3 ]. According to the most recent records of the Health Insurance Review and Assessment Service in South Korea, denosumab is the most frequently prescribed anti-osteoporosis drug, accounting for 30% of the entire market share of osteoporosis medications.…”
Section: Introductionmentioning
confidence: 99%